2021
DOI: 10.1177/10406387211001869
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and immunohistochemical findings in an outbreak of systemic toxoplasmosis in a mob of red kangaroos

Abstract: Toxoplasma gondii is a zoonotic protozoan pathogen that infects many endothermic vertebrates, including humans; the domestic cat and other felids serve as the definitive host. Macropodids are considered highly susceptible to toxoplasmosis. Here, we describe the clinical, pathologic, and immunohistochemical findings of an outbreak of systemic toxoplasmosis in a mob of 11 red kangaroos ( Macropus rufus), with high morbidity (73%) and mortality (100%) rates. Affected animals had either severe and rapidly deterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 36 publications
1
24
0
3
Order By: Relevance
“…To our knowledge, this is the first time the parasite load is measured in tissues of infected wallabies. Carossino et al ( 18 ) also performed qPCR but only reported mean CT. Supporting the findings we describe, they demonstrated that the lung was the organ with the highest parasite load, followed by the liver as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first time the parasite load is measured in tissues of infected wallabies. Carossino et al ( 18 ) also performed qPCR but only reported mean CT. Supporting the findings we describe, they demonstrated that the lung was the organ with the highest parasite load, followed by the liver as well.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the findings we describe, they demonstrated that the lung was the organ with the highest parasite load, followed by the liver as well. The spleen was not included in real-time PCR ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some animal species show a higher susceptibility to this parasite and develop fatal toxoplasmosis [ 6 ]. Lemurs, New World non-human primates (NWNHPs), and Australasian marsupials are highly susceptible to toxoplasmosis with frequent sudden death when infected [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kangaroos commonly occur in regions that are inhabited and used by livestock and humans, and which include surface waters that are used as a drinking water source. As a ruminant animal, the kangaroo has been identified as hosting several human pathogens within their gut microbiota, with the potential to cause zoonotic harm to humans in rare cases [5,6] Due to the diversity of gut microbiota and complex bacterial signatures between animals and humans, microbial source tracking (MST) methods have been developed to identify bacterial taxa that may be novel in order to distinguish animals that contribute to freshwater faecal pollution [7]. As animal faecal contamination is less distinguishable as a point source, identifying the faecal pollution's source once it enters the waterway is difficult [8].…”
Section: Introductionmentioning
confidence: 99%
“…Kangaroos commonly occur in regions that are inhabited and used by livestock and humans, and which include surface waters that are used as a drinking water source. As a ruminant animal, the kangaroo has been identified as hosting several human pathogens within their gut microbiota, with the potential to cause zoonotic harm to humans in rare cases [ 5 , 6 ]…”
Section: Introductionmentioning
confidence: 99%